Metabolic therapy with PEG-arginase induces a sustained complete remission in immunotherapy-resistant melanoma - De Santo, Carmela; Cheng, Paul; Beggs, Andrew; Egan, Sharon; Bessudo, Albert; Mussai, Francis (BioMed Central, 2018)
Background